Evaluasi Pengembangan Disaster Recovery Center untuk Data Center Universitas Udayana - Shobirin, Kheri Arionadi; Sastra, Nyoman Putra; Sudarma, Made (Majalah Ilmiah Teknologi Elektro, 2021)
Data Center has a vital and strategic role in supporting university operations. Based on Government Regulation No.17 of 2019 article 20 section 1: Every Data Center owner must have a Disaster Recovery Center. Evaluation of Disaster Recovery Center Development for Udayana University Data Center conducted by considering aspects of natural threats, human threats, environmental threats, existing Data Center specification, virtualization, and cloud technology used to maintain the availability of Data Center services for Udayana University with the most efficient development costs.  Using cost comparation for DRC development and operation for 3 years, found that implementation cost of Cloud DRC 3 times higher compare to Conventional DRC. High cloud computing cost contribute 67% of Cloud DRC cost structure.